Pragmatic cooperation instead of a strategic partnership: The current status and perspectives for German-Polish relations - Kai-Olaf Lang (Stiftung Wissenschaft und Politik (SWP), 2004)
German-Polish relations are currently going through a difficult phase. The announce-ment by expelled Germans, to file claims for restitution in Polish and international courts, and the demand made by the Polish Parliament for war reparations, have ensured that there will be turbulent relations between the two countries. Although both the German and Polish governments distanced themselves from those demands, tension in bilateral relations in the near term should be expected, in part because in Poland there are growing doubts about whether a long-term orientation towards Germany makes sense. At the same time, since Poland's accession to the European Union on May 1, 2004, there has not been a big project that binds both sides together in a constructive way. Therefore, the approach of a less ambitious 'pragmatic coopera-tion' of both countries seems to be more realistic than one with a specific two-party relationship, a type of 'strategic partnership.'(SWP Comments / SWP)
Keywords: 320